The Opposition of Language and Speech: A Structural and Paradigmatic Analysis (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article analyzes the structural, semantic, and functional differences between language (langue) and speech (parole) within the framework of modern linguistic approaches. Language is examined as a social memory and a system of signs, while speech is treated as an individual, dynamic realization of this system. The study investigates how basic linguistic units — phonemes, morphemes, lexemes, and structural models — function in the paradigmatic system of language and are realized syntagmatically in speech. The analysis integrates concepts from structural linguistics, functional grammar, and discourse theory, highlighting the contextual operation of language units. This study strengthens theoretical perspectives in linguistics and proposes methodological applications suitable for further research in discourse and communication studies.